Simulation and modeling current technologies and applications - El Sheikh, Asim Abdel Rahman; Al Ajeeli, Abid; Abu-Taieh, Evon M. O. (Hershey, Pennsylvania IGI Publishing, 2008)
Offers insight into the computer science aspect of simulation and modeling while integrating the business practices of SM. Includes current issues related to simulation, such as: Web-based simulation, virtual reality, augmented reality, and artificial intelligence, combining different methods, views, theories, and applications of simulations.
Keywords: Computer simulation; Electronic books